2020
DOI: 10.1002/jez.2343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiO2 nanoparticles on the life‐table parameters, antioxidant indices, and swimming speed of the freshwater rotifer Brachionus calyciflorus

Abstract: Titanium dioxide nanoparticles (nTiO2) have raised environmental concerns and display potential hazards to aquatic organisms and even humans. However, only a few reports tested the toxicity of nTiO2 to rotifers. In the present study, acute and chronic toxicity of nTiO2 to the freshwater rotifer Brachionus calyciflorus was investigated at different temperatures. At 25°C, the 24 and 48‐hr LC50 was 117.14 and 60.11 mg/L, respectively. At 15°C, 20°C, 25°C, and 30°C, exposure to nTiO2 significantly decreased life e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…141 With greater acute toxicity (Fig. 5A), Ag NPs stimulated more to compensate for a homeostasis imbalance, 143 encouraged faster swimming to escape a dangerous environment, 142 or caused hyperactivity as observed in aquatic invertebrate larvae, including Daphnia magna . 144…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…141 With greater acute toxicity (Fig. 5A), Ag NPs stimulated more to compensate for a homeostasis imbalance, 143 encouraged faster swimming to escape a dangerous environment, 142 or caused hyperactivity as observed in aquatic invertebrate larvae, including Daphnia magna . 144…”
Section: Resultsmentioning
confidence: 99%
“…and impairments (e.g., visual, 140 neuromotor deficits, 141 etc.). Conversely, increased swimming speed (negative SSA) may indicate escape reactions from hazardous environments, 138,142 psychostimulant action, or anxiety-like behavior. 141 With greater acute toxicity (Fig.…”
Section: Bioaccumulation Of Ps and Ag Nanoparticles Acute Toxicity An...mentioning
confidence: 99%
“…These findings suggested that high temperatures may increase CPZ toxicity to rotifers. Similarly, the toxicity of nTiO 2 and imidacloprid to B. calyciflorus with increasing temperature [ 66 , 67 ], as well as the toxicity of terbufos, trichlorfon, and imidacloprid to Palaemonetes spp. , Cyprinodon variegatus and Isonychia bicolor [ 68 , 69 ], and the toxicity of an ethoprop- malathion mixture to Oncorhynchus kisutch [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. similis has a higher SS than freshwater rotifers species such as Brachionus calyciflorus , Cephalodella gibba , Epiphanes senta , Lecane furcata , Lecane luna , Lecane pyriformis , Lecane hamata and Lepadella patella (0.17–0.54 mm s −1 ). On the other hand, it is lower than Asplanchna girodi , Euchlanis dilatata and Plationus patulus (0.69–0.98 mm s −1 ) (Dong et al, 2020; Rico‐Martínez & Snell, 1997; Santos‐Medrano et al, 2001). Overall, SS of P. similis recovered over time and, in some cases, was higher than that observed in controls.…”
Section: Discussionmentioning
confidence: 99%